2005
DOI: 10.1042/bj20050663
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the chemistry of conjugation of poly(ethylene glycol) to Hb on the oxygen-binding and solution properties of the PEG-Hb conjugate

Abstract: Our recent studies on PEG-Hb [poly(ethylene glycol)-Hb] conjugates generated by thiolation-mediated maleimide-chemistry based PEGylation demonstrated that the vasoactivity of the PEG-Hb conjugates is a function of the configuration of the PEG chains on the surface of the protein and is independent of the PEG/protein-mass ratio [Manjula, A. G. Tsai, Intaglietta, H.-C. Tsai, Ho, Smith, Perumalsamy, Kanika, Friedman and Acharya (2005) Protein J. 24, 133-146]. A Hb conjugated with six PEG5k chains (SP-PEG5k)6-Hb, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 38 publications
3
57
0
Order By: Relevance
“…Compared to values reported in the literature [29], the P 50 for purified hHb is similar. Hu et al [10] reported a P 50 of 14 torr and a cooperativity of 2.8 for hHb, whereas [29] reported a P 50 of 15.1 torr and a cooperativity of 2.97 for hHb. The difference between these published values and the values in this work are easily explained in terms of the different buffer conditions used for measuring the oxygen binding equilibria.…”
Section: Purification Of Hbmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to values reported in the literature [29], the P 50 for purified hHb is similar. Hu et al [10] reported a P 50 of 14 torr and a cooperativity of 2.8 for hHb, whereas [29] reported a P 50 of 15.1 torr and a cooperativity of 2.97 for hHb. The difference between these published values and the values in this work are easily explained in terms of the different buffer conditions used for measuring the oxygen binding equilibria.…”
Section: Purification Of Hbmentioning
confidence: 99%
“…The difference between these published values and the values in this work are easily explained in terms of the different buffer conditions used for measuring the oxygen binding equilibria. For example, the oxygen binding equilibria of hHb in this study was measured in Hemox buffer, whereas [10] used PBS (pH = 7.4) as the measurement buffer. These changes in the buffer composition explain the observed variation in P 50 .…”
Section: Purification Of Hbmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it can be concluded that site selectivity of PEGylation is also not the determinant of the PEGylation induced in vivo neutralization of the vasoconstrictive activity of acellular Hb. Besides, we have hexaPEGylated Hb by direct PEGylation using reductive alkylation chemistry (Hu et al 2005) and active ester chemistry , and all the hexaPEGylation protocols induce the neutralization of the vasoactivity of Hb. Though all hexaPEGylated Hbs are high oxygen affinity Hbs, there were noticeable differences in the oxygen affinity of these molecules and also in the COP, but that does not seem to have much correlation with the attenuation of natural vasoconstriction brought upon by the presence of intravascular acellular Hb.…”
Section: Hexapegylation With Peg 5k But Not Extension Armmentioning
confidence: 99%
“…Accordingly, we have been considering the use of low O 2 -affinity Hbs instead of using normal adult human Hb as substrates for the generation of PEGylated Hbs using the same protocols discussed above (19)(20)(21)(22).…”
mentioning
confidence: 99%